2009
DOI: 10.1007/s00586-009-1048-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of sacroplasty in sacral insufficiency fractures: a review of the literature

Abstract: Sacral insufficiency fractures (SIFs) are an increasingly recognised cause of back pain in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 28 publications
3
36
1
18
Order By: Relevance
“…Presently there are many techniques of sacroplasty differing in surgical approach, with or without balloon and different cement volumes. A review of Bayley et al showed the significant pain reduction after sacroplasty, this was also seen in our first results immediately postoperatively [13]. A biomechanical study of Richards et al showed that this technique does not restore the strength or stiffness of the sacrum regardless of the volume or location of cement [14].…”
Section: Discussionsupporting
confidence: 54%
“…Presently there are many techniques of sacroplasty differing in surgical approach, with or without balloon and different cement volumes. A review of Bayley et al showed the significant pain reduction after sacroplasty, this was also seen in our first results immediately postoperatively [13]. A biomechanical study of Richards et al showed that this technique does not restore the strength or stiffness of the sacrum regardless of the volume or location of cement [14].…”
Section: Discussionsupporting
confidence: 54%
“…In the long-axis technique, a long trace is passed along the sacral wing in the caudocephal direction; in the short-axis technique, a posterior-anterior approach is used, with a trajectory similar to that of a sacral wing screw. It was reported that in the long-axis technique, PMMA can be directly injected along the fracture line, but the procedure is associated with a potential risk of PMMA leakage into the sacral foramen and perforation of the anterior cortex (3,4,6,24,21). It is reported that the lateral zone of the sacrum is the safest zone for sacroplasty (1,11).…”
Section: Discussionmentioning
confidence: 99%
“…Girişimsel radyolojide sakral yetmezlik fraktürlerinde sement ile sakroplasti hızlı ağrı palyasyonu sağladığı için uygun vakalarda uygulanmaktadır (14).…”
Section: Minimal İnvaziv İşlemlerunclassified